Matchplay characteristics of Grand Slam tennis: implications for training and conditioning. Issue 19 (1st October 2016) - Reid, Machar; Morgan, Stuart; Whiteside, David
ABSTRACT: The purpose of this study was to probe the sex-based differences in the stroke and movement dynamics of Grand Slam hard-court tennis. Player and ball tracking data were collated for 102 male and 95 female players during the 2012–2014 Australian Open tournaments. Serve, serve return, groundstroke and movement data were compared between sexes. Serve statistics were the subject of the largest differences, with males achieving significantly faster speeds, aces and unreturned serves while also winning a greater percentage of service points. When returning serve, women contacted the ball closer to the net, lower to the ground and achieved flatter ball trajectories than males. Groundstroke frequencies were similar between sexes, although males hit with greater speed, flatter trajectories and impacted more shots inside the baseline. Distance covered per set or during points won or lost was not sex dependent, yet men exhibited faster average movement speeds. These findings highlight the need for sex-specific training and practice designs that cater to the different stroke dynamics, particularly in relation to the first serve and serve-return, as well as movement speeds.